Heading direction tracks internally directed selective attention in visual working memory - Thom, JL; Nobre, AC; van Ede, F; Draschkow, D (MIT Press Direct, 2023)
We shift our gaze even when we orient attention internally to visual representations in working memory. Here, we show the bodily orienting response associated with internal selective attention is widespread as it also includes the head. In three virtual reality experiments, participants remembered 2 visual items. After a working memory delay, a central color cue indicated which item needed to be reproduced from memory. After the cue, head movements became biased in the direction of the memorized location of the cued memory item-despite there being no items to orient toward in the external environment. The heading-direction bias had a distinct temporal profile from the gaze bias. Our findings reveal that directing attention within the spatial layout of visual working memory bears a strong relation to the overt head orienting response we engage when directing attention to sensory information in the external environment. The heading-direction bias further demonstrates common neural circuitry is engaged during external and internal orienting of attention.